2012
DOI: 10.1007/s10162-012-0318-3
|View full text |Cite
|
Sign up to set email alerts
|

Directional Asymmetries and Age Effects in Human Self-Motion Perception

Abstract: Directional asymmetries in vestibular reflexes have aided the diagnosis of vestibular lesions; however, potential asymmetries in vestibular perception have not been well defined. This investigation sought to measure potential asymmetries in human vestibular perception. Vestibular perception thresholds were measured in 24 healthy human subjects between the ages of 21 and 68 years. Stimuli consisted of a single cycle of sinusoidal acceleration in a single direction lasting 1 or 2 s (1 or 0.5 Hz), delivered in sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
109
5
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 94 publications
(133 citation statements)
references
References 52 publications
(57 reference statements)
18
109
5
1
Order By: Relevance
“…We found no significant difference between the detection thresholds of younger and older subjects undergoing 0.5 Hz earth-vertical sinusoidal rotations determined using a two-alternative, two-interval forced choice paradigm. This confirms an earlier study of detection thresholds, which also found no relationship to age while using a somewhat different, single-interval paradigm consisting of solitary raised-cosine rotations at 0.5 Hz (Roditi and Crane 2012). Others have also failed to find a difference with age, with one study finding that thresholds to motion along a 0.5 Hz triangular velocity trajectory about the earth-vertical axis remained stable across a range of ages (Seemungal et al 2004).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We found no significant difference between the detection thresholds of younger and older subjects undergoing 0.5 Hz earth-vertical sinusoidal rotations determined using a two-alternative, two-interval forced choice paradigm. This confirms an earlier study of detection thresholds, which also found no relationship to age while using a somewhat different, single-interval paradigm consisting of solitary raised-cosine rotations at 0.5 Hz (Roditi and Crane 2012). Others have also failed to find a difference with age, with one study finding that thresholds to motion along a 0.5 Hz triangular velocity trajectory about the earth-vertical axis remained stable across a range of ages (Seemungal et al 2004).…”
Section: Discussionsupporting
confidence: 89%
“…It was uncertain based on their study whether the changes seen with aging were specific to the higher frequency or might have actually been more closely dependent on the higher accelerations also inherent in that higher stimulus. As our discrimination stimulus tested function at the same frequency but higher accelerations, and we found no elevation of thresholds with aging, it could be concluded that the effect seen by Roditi and Crane (2012) may have indeed been determined by frequency more than acceleration.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…To simplify interpretation of results, we did not perform the scaling of the biased-reduced estimates (Chaudhuri and Merfeld 2013) to further improve accuracy, but this could easily be done in combination with the approaches described in this paper. For simplicity, we opted not to include a nonlinear asymmetry (Roditi and Crane 2012a) or a lapse rate (Wichmann and Hill 2001a), though either could be readily included as independent effects when necessary.…”
Section: Methodsmentioning
confidence: 99%